AN ANALYSIS OF ENGLISH SLANG WORDS DISCUSSED BY SLANG CONTENT CREATORS ON TIKTOK - Ainun Nisa Yuniar; Suwandi Suwandi; AB Prabowo KA (Program Studi Pendidikan Guru Sekolah Dasar, Universitas PGRI Semarang, 2023)
This study discusses the analysis of the meaning and types of English slang words used by English speaking people on TikTok. This study also discusses the contribution of English slang words in language learning. There are 50 data that have been analyzed by researchers. The methodology of this research was qualitative research. The study consisted of three steps, they were; reading, selecting, and classifying the data. To identify the types of slang words, the researcher used the theory of Michael Munro (2007). The researcher also used online and manual to find the meaning of English slang words. Researchers found six out of eight types of slang words on TikTok. They are United States slang, Canadian slang, Australian slang, New Zealand slang, South African slang, and Irish slang. The researcher did not find slang words that belong to the type of Caribbean slang and South Asian slang. There are 16 United States slang words, 3 Canadian slang words, 11 Australian slang words, 10 New Zealand slang words, 5 South African slang words, and 5 Irish slang words. The United States slang type dominates the type of slang used by English speaking people on TikTok.